Detection of respiratory syncytial virus (RSV) at birth in a newborn with respiratory distress. Issue 10 (18th August 2017) - Manti, Sara; Cuppari, Caterina; Lanzafame, Angela; Salpietro, Carmelo; Betta, Pasqua; Leonardi, Salvatore; Perez, Miriam K.; Piedimonte, Giovanni
Abstract: Respiratory syncytial virus (RSV) is the most common respiratory pathogen in infants and young children. From the nasopharyngeal or conjunctival mucosa of infected individuals, RSV spreads to the lower respiratory tract causing acute bronchiolitis and pneumonia after an incubation period of 4‐6 days. In addition to its well‐documented tropism for the airway epithelium, it has been shown previously that RSV can also spread hematogenously and efficiently infect extrapulmonary tissues of human hosts. Furthermore, it has been shown in animal models that RSV can spread transplacentally from the respiratory tract of a pregnant mother to the lungs of the fetus. This report describes a documented case of neonatal RSV infection strongly suggestive of prenatal transmission of this infection in humans from an infected mother to her offspring.